Determinants and prognostic value of B-type natriuretic peptide in patients with aortic valve stenosis. (1st March 2017) - Nguyen, Virginia; Cimadevilla, Claire; Arangalage, Dimitri; Dehoux, Monique; Codogno, Isabelle; Duval, Xavier; Tubiana, Sarah; Vahanian, Alec; Messika-Zeitoun, David
Abstract: Background: The prognostic value of N-terminal fragment of pro B-type natriuretic peptide (Nt-proBNP) in aortic stenosis (AS) is still being debated. We sought to evaluate the determinants of Nt-proBNP in AS and its prognostic value in asymptomatic patients. Methods: Patients with pure isolated at least mild degenerative AS enrolled in our prospective cohort (2006–2013) constituted our population. Clinical and biological measurements as well as echocardiographic evaluations were performed at study entry for all patients. Severe AS was defined by a valve area < 1 cm 2 . Asymptomatic patients were contacted every six months and seen every year. The occurrence of AS-related events (sudden death, congestive heart failure or new onset of symptoms) within two years was recorded prospectively. Results: We enrolled 809 patients. Nt-proBNP increased with AS severity ( p < 0.0001) and symptomatic status ( p < 0.0001) but there was a wide overlap between groups of AS severity or symptomatic status. Nt-proBNP was the result of complex interactions between multiple determinants, including AS severity and symptomatic status but also age ( p = 0.0008), history of coronary artery disease ( p = 0.03), rhythm ( p = 0.007) and diastolic function ( p < 0.0001). Consequently, in asymptomatic patients with moderate/severe AS, normal ejection fraction and in sinus rhythm, Nt-proBNP was associated with AS-related events in univariate analysis ( p = 0.009) but not after adjustment for AS severity ( p = 0.12). Repeated Nt-proBNP measurements at one year did not improve their predictive value ( p = 0.43). Conclusion: This study highlights the limitations of Nt-proBNP in AS and raises caution regarding its use, at least as a single factor, in the decision-making process regarding asymptomatic patients with AS.